DEVELOPMENT AND EVALUATION OF THE EFFECTIVENESS OF INDIVIDUAL HYGIENE MEASURES IN PATIENTS UNDERGOING ORTHODONTIC TREATMENT - Khabibjonova, Yoqutkhon (Medical science of Uzbekistan, 2025)
Relevance. In recent years, the study of oral microflora has become a relevant scientific direction in dentistry and orthodontics. Oral microflora plays an important role in human health, as it is directly associated with diseases such as caries, gingivitis, periodontitis, and stomatitis. During orthodontic treatment, the presence of fixed or removable orthodontic appliances changes the balance of the microflora, leading to an increase in the number of cariogenic and periodontal pathogenic bacteria. Research shows that if oral hygiene is not maintained, orthodontic appliances can intensify plaque accumulation, causing inflammation and demineralization. In this study, more than 30 scientific works from major international sources such as Scopus, Web of Science, and PubMed, including those by Melsen, Lucchese, Ristic, Perinetti, and Kolesnikova, were analyzed. Both fixed and removable orthodontic appliances, as well as hygienic tools (toothbrushes, interdental brushes, fluoride toothpaste, dental floss, and chlorhexidine solution), were studied. Clinical indicators such as the supragingival bacterial matrix index and gingival index were evaluated. Data were analyzed using Student’s t-test and ANOVA methods. The article noted that the amount of Lactobacillus and other cariogenic bacteria was higher in patients with fixed orthodontic appliances. The study showed that orthodontic appliances placed in the oral cavity alter the balance of microflora and increase the growth of cariogenic bacteria. Fixed appliances cause a higher degree of pathogenic colonization, while the effect of removable appliances is relatively milder. After removal of the appliances, a tendency toward restoration of the microflora was observed. Therefore, orthodontists should regularly monitor patients’ oral hygiene and implement individual hygiene programs. In the future, the use of antimicrobial materials and improved hygienic approaches can further enhance the effectiveness of orthodontic treatment.